Augmentation of free amino acids in eggs of red snapper, Lutjanus campechanus as part of the induced spawning protocol. (29th March 2013) - Hastey, Ryan; Phelps, Ronald; Davis, Allen; Cummins, Keith
Abstract An attempt was made to increase free amino acids (FAA) concentrations in eggs of red snapper Lutjanus campechanus as part of an induced spawning protocol. Mature female red snapper were given intramuscular injections of human chorionic gonadotropin (HCG) at a 1100 IU kg−1 of female body weight. Immediately after the HCG injection, one set of females received an intramuscular injection of FAA in a buffered saline solution at a dose of 20 mg FAA cocktail kg−1 of body weight. The FAA cocktail was 25% isoleucine, 25% leucine, 25% lysine and 25% valine on a molecular weight basis. A second set of fish did not receive the FAA supplement. Both sets of fish were equally successful in spawning with ovulation occurring 21–32.5 h post injection. Injection of FAA into brooders as eggs began final maturation and hydration resulted in an increase in leucine (nmoles mg egg−1) and a slight increase in isoleucine (nmoles egg−1) in recently ovulated eggs. FAA supplementation via brood injection altered FAA utilization rates by embryos and during larval development, resulted in a greater yolk sac and oil globule reserve in larvae as they approached the time of first feeding.